2007
DOI: 10.1111/j.1465-3435.2007.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Digital Divide: impacts on student‐tutor relationships

Abstract: This article emerged from a series of debates and workshops on the impact of the Digital Divide on educational practice at the ‘Futures of Learning: New Learning Paradigms Conference’ in Paris. The conceptualisation of the Digital Divide into the ‘haves’ and the ‘have‐nots’, with a perception of the economically developed world as ‘high tech’ and the developing and underdeveloped worlds as ‘low tech’, is no longer tenable. Building on the recognition based on mounting evidence that old perceptions of the Digit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 20 publications
1
24
0
2
Order By: Relevance
“…Clearly, both groups of students have access and do not have access to the Internet, debunking the assumption that all online students have regular access to the Internet and that all paper-based respondents are likely not to have regular access. This confirms research by, amongst others, Brown and Czerniewicz (2010), Czerniewicz (2004), Underwood (2007), and Warschauer (2002), supporting the idea that access to computers and the Internet is a multidimensional phenomenon and that the strict binary of "haves" and "have-nots" is not a usable construct.…”
Section: Access To the Internetsupporting
confidence: 67%
See 1 more Smart Citation
“…Clearly, both groups of students have access and do not have access to the Internet, debunking the assumption that all online students have regular access to the Internet and that all paper-based respondents are likely not to have regular access. This confirms research by, amongst others, Brown and Czerniewicz (2010), Czerniewicz (2004), Underwood (2007), and Warschauer (2002), supporting the idea that access to computers and the Internet is a multidimensional phenomenon and that the strict binary of "haves" and "have-nots" is not a usable construct.…”
Section: Access To the Internetsupporting
confidence: 67%
“…Underwood (2007, p. 214) further states that the notion of the digital divide "is a simplistic model even at an economic level and that it is better to think of information-based economic nodes, within and across regions and within and across countries." A more nuanced understanding of the digital divide must also take into account the "second-level digital divide," capturing the skills dimension of access to technology (Underwood, 2007, p. 214), the different levels of digital literacy, and the divides resulting from the use of English as the language of communication in many online educational platforms (Underwood 2007, p. 215). Warschauer (2002 states that the "notion of the binary divide between the haves and the have-nots is thus inaccurate and can even be patronising as it fails to value the social resources that diverse groups bring to the table.…”
Section: That Inclusionmentioning
confidence: 99%
“…In fact, it has been widely suggested that the traditional socio-economic differences that have dictated access to technology are not the fundamental factor in digital inclusion. Authors such as Prensky (2001), Madden et al (2007) and Underwood (2007) have proposed that the digital divide is a complex of interacting physical, digital, human, and social resources that is based instead on generationally related differences in technology use and skills (e.g. "digital natives" vs "digital immigrants").…”
Section: Digital Inclusionmentioning
confidence: 99%
“…Many researchers have highlighted the need for consideration of variation of both access to and use made of the Internet within populations, to avoid acceptance of ambit claims made about the role of the Internet as if it was similarly used by whole generations of people (Brown & Czerniewicz, 2010;Ferro, Dwivedi, Gil-Garcia, & Williams, 2010;Fourie & Bothma, 2006;Hargittai, 2010;Hargittai & Hinnant, 2008;Helsper, 2008;Helsper & Eynon, 2010;Kennedy et al, 2010;Mertens & d'Haenens, 2010;Rideout et al, 2010;Selwyn, 2008b;Thinyane, 2010;Underwood, 2007;Vaidhyanathan, 2008;Warschauer & Matuchniak, 2010).…”
Section: The Digital Dividementioning
confidence: 99%